Experimental investigation of convective heat transfer coefficient during downward laminar flow condensation of R134a in a vertical smooth tube - Dalkilic, A. S.; Yildiz, S.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
This paper presents an experimental investigation of laminar film condensation of R134a in a vertical smooth tube having an inner diameter of 7-8.1 mm and a length of 500 mm. Condensation experiments were performed at mass fluxes of 29 and 263 kg m(-2) s(-1). The pressures were between 0.77 and 0.1 MPa. The heat transfer coefficient, film thickness and condensation rate during downward condensing film were determined. The results show that an interfacial shear effect is significant for the laminar condensation heat transfer of R134a under the given conditions. A new correlation for the condensation heat transfer coefficient is proposed for practical applications. (C) 2008 Published by Elsevier Ltd.
Keywords: Condensation; Heat transfer coefficient; Downward flow; Laminar flow; SURFACE CONDENSATION; STEAM; GAS; Thermodynamics; Engineering; Mechanics